A prayer for the dying : a novel - O'Nan, Stewart, 1961- (Henry Holt & Co., 1999)
Set in Friendship, Wisconsin, just after the Civil War, A Prayer for the Dying tells of a horrible epidemic that is suddenly and gruesomely killing the town's residents and setting off a terrifying paranoia. Jacob Hansen, Friendship's sheriff, undertaker, and pastor, is soon overwhelmed by the fear and anguish around him, and his sanity begins to fray. Dark, poetic, and chilling, A Prayer for the Dying examines the effect of madness and violence on the morality of a once-decent man.